Dynamical effective parameters of elastic superlattice with strong acoustic contrast between the constituents - Zubov, Y.; Bahram Djafari-Rouhani; Krokhin, A. (Физика низких температур, 2018)
Analytical formulas are obtained for frequency-dependent effective elastic modulus and effective mass density for a periodic layered structure. The proposed homogenization procedure is valid at sufficiently high frequencies well above the lowest band gap in the acoustic spectrum of the structure. It is shown that frequencydependent effective parameters may take negative values either in different regions of frequencies or in the same
quite narrow region. This property demonstrates that 1D elastic structure may behave in the limit of small Bloch
wave vectors as a double-negative acoustic metamaterial. Отримано аналітичні формули для частотно-залежних ефективного модуля пружності та ефективної щільності періодичної шаруватої структури. Запропонована процедура гомогенізації справедлива при досить високих частотах, що
перевищують частоту першої забороненої зони в акустичному
спектрі структури. Показано, що залежні від частоти ефективні параметри можуть набувати від’ємних значень або в
різних частотних областях, або в одній досить вузькій області. Ця властивість показує, що одновимірна пружна структура в межі малих блоховських хвильових векторів може поводитися як акустичний метаматериал, у якого обидва ефективні параметри від’ємні. Получены аналитические формулы для частотнозависимых эффективного модуля упругости и эффективной
плотности периодической слоистой структуры. Предложенная процедура гомогенизации справедлива при достаточно
высоких частотах, превышающих частоту первой запрещенной зоны в акустическом спектре структуры. Показано, что
зависящие от частоты эффективные параметры могут принимать отрицательные значения либо в различных частотных
областях, либо в одной достаточно узкой области. Данное
свойство показывает, что одномерная упругая структура в
пределе малых блоховских волновых векторов может вести
себя как акустический метаматериал, у которого оба эффективных параметра отрицательны.